EFL Students’ Voice on the Use of Spotify Application toward Students’ Pronunciation - Melvina, Melvina; Bella, Dian Nusa; ikhsan, Muhammad Khairi (Linguistics and ELT Journal, 2023)
Majority of Senior High School students thought that pronunciation is challenging. However, the use of application in the learning process could effectively assist students. The aim of this research is to identify the perceptions of students about the use of Spotify to learn pronunciation. The survey research was used to carry out this study. Thirty senior high school students were invited to fill the online questionnaire. After collecting the data, the researchers analyzed the data by using SPSS and presented descriptively. The result revealed that the students as the sample gave positive responses about the use of Spotify as media of learning English especially to learn pronunciation. English songs on Spotify could be useful for students in the process of learning English, it could be an easy and simple media for students to learn English. It was suggested to English teachers to find out students’ interests so the learning process would be more enjoyable and make students could receive the lessons given well